The consumer price index : issues and alternatives - Cagan, Phillip; Moore, Geoffrey Hoyt. (Washington, D.C. : American Enterprise Institute, 1981)
This volume assesses the merits and demerits of the Consumer Price Index in view of widespread criticisms that it has overstated the rate of inflation, especially as an index for escalating wages, social security, and federal pension payments. The book describe the purpose, uses, and construction of the CPI and compare it with various alternative measures of price changes.
Includes bibliographical references.
mf24/01/2019
Loans
Keywords: Consumer price indexes; Prices; Economic conditions; Inflation